Coal cleaning: A viable strategy for reduced carbon emissions and improved environment in China? - Solveig Glomsrød; Wei Taoyuan (Statistics Norway, Research Department, 2003)
China is a dominant energy consumer in a global context and current energy forecasts emphasise that China's future energy consumption also will rely heavily on coal. The coal use is the major source of the greenhouse gas CO2 and particles causing serious health damage. This paper looks into the question if coal washing might work as low cost strategy for both CO2 and particle emission reductions. Coal washing removes dirt and rock from raw coal, resulting in a coal product with higher thermal energy and less air pollutants. Coal cleaning capacity has so far not been developed in line with the market potential. In this paper an emerging market for cleaned coal is studied within a CGE model for China. The macro approach catches the repercussions of coal cleaning through increased energy efficiency, lower coal transportation costs and crowding out effect of investments in coal washing plants. Coal cleaning stimulates economic growth and reduces particle emissions, but total energy use, coal use and CO2 emissions increase through a rebound effect supported by the vast reserve of underemployed labourers. A carbon tax on fossil fuel combustion has a limited effect on total emissions. The reason is a coal leakage to tax exempted processing industries.
Keywords: 330; Coal; China; carbon tax; CGE